Institutionalization Process Dymension of Political Parties (Study of Institutionalization of Golkar Party in South Sulawesi Province) - Gustiana A. Kambo (Journal of Society and Governance, 2017)
AbstractThis study was intended to describe the dynamics of institutional processes run by the political parties in strengthening the position and role in the democratic system. Institutional process oriented by the party dynamics in building political strength that comes from internal and external mechanisms. In addition, it is understood that the institutionalization built a consensus of shared internal consolidation of all party members. Study of institutionalization in this research using the idea of Guelermo O'Donnell and Vicky Randall stated that the process of structural stabilization of the political parties are use the strong patterns of behavior and culture. While the method used is the thought of Edmund Husserl emphasizes the qualitative method in which phenomenological tradition assumes the subjective meaning based on real observations of the social and political orders. The results of this research showed that there is a transformation of public understanding, especially at the credibility on political parties. The credibility can be gained when a political party is particularly strong in the party institutionalization.